Discurso socioeducativo - jogo, fuga e batalhas: um estudo sobre práticas, técnicas e procedimentos do atendimento ao adolescente infrator - Ronalte Vicente da Silva (2020)
The Socio-educational Discourse is the object of analysis of this dissertation. Inspired by Michel Foucault, this research understands by socio-educational discourse the practices, techniques and procedures adopted in assisting the adolescent who is responsible for the infraction. For this, it was analyzed a file composed of nineteen (19) processes (handbook, files) of execution of socio-educational measures of semiliberty and internment. These files were deposited between 2002 and 2017 at the Children and Youth Court of Belo Horizonte, Minas Gerais, Brazil. The aim of the study was to analyze which subject is produced when the notion of socio-educational assumes the legal and pedagogical orientation about adolescents. As a theoretical framework, Michel Foucault's contributions were used, especially those related to disciplinary power and standardization practices. Methodologically, the study was based on some method precautions contained in Michel Foucault's book, I, Pierre Riviere, Having Slaughtered My Mother, My Sister, and My Brother: A Case of Parricide in the 19th Century, to adopt the first principles of materiality organization. In addition to this book, the Class of February 28, 1973, of the course The Punitive Society, was also used. Although there is no linear or static methodology in Foucault, nor a prescription, these two texts served as prescriptive-methodological references, since, from them, tools were forged for treatment, organization, reading and study of the infraction processes, as Foucault proceeded. Thus, the study was dedicated to analyzing what was said, what was excessively said, about teenagers, avoiding what could be called schooling of speeches. As a result of the analysis of the processes, it allowed us to identify three procedures that make up the sayings regarding the socio-educational subject, namely: (i) the battles between technicians, judges and prosecutors; (ii) the discourse of the technicians; (iii) the teenager learns to play the legal game. Such procedures reveal a dispute of interests over adolescents that, among other things, run through issues of integral protection, poverty, work, accountability, but also obedience or youth transgression. Keywords: Socio-educational measures. Adolescent Offender. Discourse. Disciplinary power and normalization. Accountability.